Cabinet secrecy - D'Ombrain, Nicholas (Canadian Public Administration, 2004)
Abstract: Cabinet secrecy is a cornerstone of the constitution of the Westminster system of government and is safeguarded by convention, common law and statute law in leading Westminster regimes. Secrecy of cabinet proceedings is very much part of the efficient constitution, but the protections afforded by convention and law are neither well understood nor particularly popular. This article examines the convention and how it differs from the common law and statute law treatments of cabinet secrecy. It considers the essential requirements for cabinet secrecy: collective decision-making; the protection of the views and opinions of ministers; and several related problems of the constitution, including the role of the cabinet as the informal executive, the use of the cabinet as an administrative coordinating mechanism, and -unique to Canada - the use of statute law to remove the courts from their traditional role of determining the balance between individual rights and those of the state. Cabinet secrecy is essential to a system of government where responsible ministers collectively decide the government's policy, but in order to play a proper role in our affairs the convention on secrecy needs to be constitutionally validated by the articulation of its purpose and scope. Sommaire: Le secret ministériel est une pierre d'angle de la constitution de Westminster, protégé par la convention constitutionnelle, la common law et la législation dans les principaux pays du système de Westminster. Le secret ministériel fait intimement partie de la constitution efficace, mais les protections procurées par la convention et la Loi ne sont ni bien comprises N particulièrement bien vues. Cet article examine la convention et comment elle se démarque de la façon dont la common law et le droit législatif interprètent le secret ministériel. Il examine les conditions essenticlles du secret ministériel: la prise de décision collective et la protection des points de vue et opinions des ministres. II examine également plusieurs problèmes connexes de la constitution, y compris le rôle du cabinet comme le pouvoir exécutif officieux; le cabinet comme un mécanisme de coordination administrative et - propre au Canada